Method for assessment of residual heat generation within preparation of spent nuclear fuel shipment from research reactors - S. H. Kadalev (Ядерна фізика та енергетика)
In the presented paper is considered the approach to an assessment of the residual heat generation within preparation of spent nuclear fuel (SNF) shipment from research reactors. A possible approach to solving the problem for residual heat generation assessment at cyclic mode of facility operation is discussed, i.e. after several periods of operation and idle time, including at different levels of the reactor operational power. The approach is scrutinized in two possible mathematical models of calculations – weekly and annually modeling of the input data for calculations. In order to prove the correctness of the calculations based on an annual operating cycle in the mathematical modeling, calculations for both models under the same operating conditions were made and comparative analysis of the results was prepared. Although such approach ensures a correct assessment at variable operation parameters (power level, duration of operation and decay time of the fuel) for the purpose of the calculations is selected an operating mode with repeated parameter values in the separate operational cycles in order to facilitate the process of analysis. As conclusion it is noted that significantly simplified calculations by annual model give correct enough and conservative results on the basis of which may be provided the necessary information according the requirements of the country which is to accept the fuel for reprocessing. On the basis of these results the selection of a cask for the SNF shipment can be done. The presented approach is applied to evaluate the residual heat generation in the SNF during its shipment preparation from the nuclear research reactor IRT-2000, Sofia, Bulgaria, to the Russian Federation within RRRFR programme.